The impact of GP-centered healthcare: a case–control study based on insurance claims data - Freytag, Antje; Biermann, Janine; Ochs, Andreas; Lux, Gerald; Lehmann, Thomas; Ziegler, Jana; Schulz, Sven; Wensing, Michel; Wasem, Jürgen; Gensichen, Jochen (Deutsches Ärzteblatt, 2016)
BACKGROUND: In Germany, enhanced primary care ('GP-centered health care') is being promoted in order to strengthen the role of GPs and improve the quality of primary care. The aim of this study was to evaluate the impact of a GPcentered healthcare program, established in 2011 in the German federal state of Thuringia, on healthcare costs, care coordination, and pharmacotherapy. - METHODS: We conducted a retrospective case-control study based on insurance claims data. Participants were followed from 18 months before the start of the program to 18 months after its introduction. The intervention and control groups were matched via propensity scores. - RESULTS: 40 298 participants enrolled in the program for a minimum of 18 months (between July 2011 and December 2012) were included in the intervention arm of the study. The mean age was 64.8 years. There was no significant difference in total direct costs (primary outcome) between cases and controls. Turning to secondary outcomes, the number of GP consultations rose sharply (+47%; p<0.001), there were less patients who consulted more than one GP (-41.4%; p<0.001), and less specialist consultations without referral (-5.8%; p<0.001) among patients in the intervention group. The number of patients who participated in Disease Management Programs (DMPs) increased (+17.7%; p<0.001), as did the number of GP home visits (+5.0%; p<0.001), specialist consultations (+4.1%; p<0.01), and the number of hospitalizations (+4.3%; p=0.006). The costs for pharmaceuticals were lowered by 3.9% (p<0.001). - CONCLUSION: The study indicates that the GP-centered healthcare program does not lead to lower direct health care costs. However, it may lead to more intense and better coordinated healthcare in older, chronically ill patients with multiple conditions. Further studies are needed on long-term effects and clinical endpoints.